Focus Attracts Attachment. (June 2022) - Carlson, Katy; Potter, David
There is growing evidence that pitch accents as well as prosodic boundaries can affect syntactic attachment. But is this an effect of their perceptual salience (the Salience Hypothesis), or is it because accents mark the position of focus (the Focus Attraction Hypothesis)? A pair of auditory comprehension experiments shows that focus position, as indicated by preceding wh -questions instead of by pitch accents, affects attachment by drawing the ambiguous phrase to the focus. This supports the Focus Attraction Hypothesis (or a pragmatic version of salience) for both these results and previous results of accents on attachment. These experiments show that information structure, as indicated with prosody or other means, influences sentence interpretation, and suggests a view on which modifiers are drawn to the most important information in a sentence.